Irisin, in women and men: blood pressure, heart rate, obesity and insulin resistance - Almeida González, Delia; Rodríguez-Pérez, María del Cristo; Fuentes Ferrer, Manuel; Cuevas Fernández, Francisco Javier; Marcelino Rodríguez, Itahisa; Cabrera de León, Antonio (Frontiers in Endocrinology, 2023)
Background: Irisin is a myokine that increases with leisure time physical activity (LTPA) and for which a cardiovascular protective role has been postulated. Our aim was to assess this role in the general population. Methods: A cross-sectional analysis was performed in a large randomly selected population sample (n=2298 women and 1529 men). Apart from age and sex, we record anthropometrics (blood pressure, heart rate, obesity), lifestyle (LTPA, smoking, alcohol), and biochemical measurements (irisin, lipid profile, insulin resistance). Correlations and regression multivariate models were used to analyze the association of irisin levels with the studied factors. Results: The variables more strongly and directly associated with irisin, adjusting the studied factors separately in women and men, were HOMA-2 (p=0.043 and p=0.001, respectively) and LTPA (p<0.001 and p=0.001, respectively). Also heart rate inversely (p=0.005 and p=0.002, respectively) and DBP directly (p<0.005 and p=0.045, respectively) were associated to irisin in both sexes. The waist/height ratio (p<0.001) was inversely associated to irisin only in women, and the alcohol drinking was directly associated (p=0.029) only in men. Conclusion: We provide new findings for irisin, such as its association with DBP and with heart rate; furthermore, in women irisin is associated to abdominal obesity, and in men is associated to the alcohol intake. We also corroborate the association of irisin with LTPA and insulin resistance. The associations detected point towards a protective role of irisin in the maintenance of cardiometabolic health.